GAMBARAN PENYEBAB KELUARGA BERISIKO STUNTING DI KABUPATEN BOJONEGORO: Overview of the Causes of Families at Risk for Stunting in Bojonegoro District - Endah Budi Permana Putri; Faradila Putri Namira; Achmad Syafiuddin (Universitas Airlangga, 2022)
The high stunting rate in Indonesia encourages the Government to make efforts to accelerate stunting reduction. One of the efforts is by assisting universities to the local government in Bojonegoro District. The purpose of this activity is to find out the factors that cause families to be at risk of stunting in Bojonegoro District. The research method used is analytic observational with a cross-sectional design. The data source for this research is secondary data in the form of PK21 Bojonegoro Regency obtained from the East Java BKKBN. The statistical analysis used was the Paired Sample T Test with α = 0.05. The results show that the type of house floor used is ceramic/granite/marble, the most used drinking water source is bottled/refill water and the most used defecation facility is a septic tank. But behind it all, there are still families who have not used a good type of floor, healthy drinking water sources and standardized defecation facilities. The conclusion of this research is that there are still families at risk of stunting in Bojonegoro District based on the parameters of the widest house floor type, drinking water sources and defecation facilities. This research is expected to contribute to the acceleration of stunting reduction in Bojonegoro District.